Antimicrobial surface coatings for polypropylene nonwoven fabrics - Çerkez, İdris; Worley, S. D.; Broughton, R. M.; Huang, T. S. (Elsevier, 2013)
Anionic and cationic N-halamine polyelectrolytes were synthesized, characterized and then immobilized onto melt-blown polypropylene fabrics having two different basis-weights. The coatings were rendered biocidal upon exposure to dilute sodium hypochlorite solution. The effect of single and multilayer deposition of the polyelectrolytes on the surfaces was investigated in terms of chlorine loadings, rechargeabilities, antimicrobial efficacies, and air permeabilities. It was found that all of the coatings provided remarkable biocidal efficacies with about six log reductions of bacteria within two mm of contact time on filters having higher basis-weight, whereas slower inactivation was observed for lower-basis weight filters due to diminished surface areas and numbers of active halogen atoms. The antimicrobial coatings reduced the air permeabilities of the filters somewhat; however, the air permeabilities of the coated swatches were comparable to those of most protective textiles. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Antimicrobial; N-halamine; Polyelectrolytes; Polypropylene; Coatings